Anomalous doping effects on stabilizing unusual phases of lithium fluoride for enhanced rechargeable battery interfaces. (15th April 2023) - Basu, Swastik; Hwang, Gyeong S.
Abstract: Implementation of high-energy-density lithium metal batteries are hampered by safety hazards like degradation of the solid electrolyte interphase (SEI) and dendrite growth, necessitating rational understanding and modification of SEI building blocks. Especially, the intrinsic role of one of its main components, lithium fluoride (LiF), has been debated with uncertainty. Herein, we present that highly lithiophilic impurities (like N, O, CO3 ) contribute towards the elusive amorphous LiF phase stability. This can be linked to their strong interaction with Li, forming well-dispersed lithium-sheathed clusters that help distort the LiF local structure surrounding them. Furthermore, a significant interplay is observed between transformation in Li-F chemical bonding and its structural distortion. Mechanically, our findings suggest that remarkable ductility is achieved by an informed choice regarding the distribution of constituent impurities in LiF. In essence, the physical origin of highly sought-after interfacial characteristics in LiF is discussed, clarifying the composition effect on phase change. Graphical abstract: Image, graphical abstract